A young woman with atypical McCune–Albright syndrome and the difficult road to recovery: a case report - Wang, Hongbin; Wang, Hao; Liu, Heng; Yang, Xin; Meng, Zhichao; Cao, Yongping (Frontiers in Surgery, 2024)
Background Fiber dysplasia is a complex condition that presents with various clinical manifestations, such as deformity, dysfunction, pathological fractures, and endocrine disorders. McCune-Albright syndrome (MAS) is a rare subtype of fiber dysplasia. This article reports a case of atypical McCune-Albright syndrome in a patient with a femoral neck fracture. Case presentation A patient with atypical McCune-Albright syndrome sustained a right femoral neck fracture and underwent multiple treatments, including total hip replacement, intravenous infusion of zoledronic acid, oral calcium supplementation, right supracondylar osteotomy, orthopedic surgery, plate and screw internal fixation for a left femoral shaft fracture, and removal of the right femoral plate. The patient also developed a submaxillary infection complicated by mandibular osteonecrosis. Conclusion Patients with MAS may experience rare complications as a result of their unique condition, regardless of whether they receive drug or surgical treatment. Therefore, personalized drug regimens and feasible surgical options are necessary.